INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) RESEARCH TRENDS IN MATHEMATICS LEARNING - Wahyuni, Astri; Kusumah, Yaya Sukjaya; Priatna Martadiputra, Bambang Avip; Purwasih, Ratni; Muhammad, Ilham; Zafrullah, Zafrullah (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The emergence of ICT in teaching and learning has contributed to improving the quality of education, because teaching and learning is ultimately an active and interesting process linked to real-world situations. ICT can be integrated into all subjects outside of physical education, including language, comprehension, math, science, and environmental science. This research examines trends and identifies publications concerning ICT in Mathematics Learning by analyzing the most prolific document sources, rankings of institutions or universities, prominent journals and articles, as well as keyword usage. Utilizing data from the Dimensions database, a total of 390 documents were gathered through the Publish or Perish (PoP) application, consolidated into a single RIS file, and analyzed using the VOSviewer application to generate network and overlay visualizations.The findings reveal an increasing trend in publications on ICT in Mathematics Learning over the past five years, with Indonesia leading in the number of documents (66),